30 Days Wild and the Relationships Between Engagement With Nature’s Beauty, Nature Connectedness and Well-Being - Richardson, Miles; McEwan, Kirsten (Frontiers in Psychology, 2018)
Recent research suggests that engagement with natural beauty (EWNB) is key to the well-being benefits of nature connectedness. The Wildlife Trust’s 30 Days Wild campaign provides a large-scale intervention for improving public engagement with nature and its beauty. The effect of 30 Days Wild participation on levels of EWNB and the relationship between EWNB, nature connectedness and happiness was evaluated during the 2017 campaign. Of the 49,000 people who signed up to the campaign, 308 people fully completed measures of EWNB, nature connection, health, happiness, and conservation behaviors at baseline, post-30 days and post-2 months. There were sustained and significant increases for scores in nature connection, health, happiness, and conservation behaviors. In addition, 30 Days Wild was the first intervention found to increase EWNB. Further, the significant increase in EWNB mediated the relationship between the increases in nature connectedness and happiness. In a supplementary study to understand the well-being benefits further (n = 153), emotional regulation was found to mediate the relationship between nature connectedness and happiness, but EWNB and emotional regulation were not related. The links between nature’s beauty, nature connectedness and well-being are discussed within an account of affect-regulation.